Upaya Meningkatkan Hasil Belajar Siswa Melalui LKPD Materi Organ Peredaran Darah Manusia Kelas 5 SDN 21 Belinyu - Rianti Septiany; M Iqbal Arrosyad; Gatot Afrianto (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This study aims to improve the learning outcomes of 5th-grade students at SD Negeri 21 Belinyu on the topic of the human circulatory system through the Use Of Studen Worksheets (LKPD). This research employs a Classroom Action Research (CAR) method, consisting of two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The subjects of this study were 22 students in the 5th grade. Data collected includes students’ test result, observations of student learning activities, and questionnaires on students’ responses to the use of LKPD. The results indicate that the use of LKPD significantly improves students’ learning outcomes. The average student score increased from 66,60 and in the first cycle to 72,05 in the second cycle. Additionally, student learning activities also improved, with students becoming more actively engaged in the learning process. The questionnaire results showed that students responded positively to the use of LKPD,finding it helpful in understanding the material. Therefor, the use of LKPD is proven to be effective in enhancing students’ learning outcomes on the topic of the human circulatory system.